Ferroelectric Compensation Effect of the Hard Electrode for the HfO2‐ZrO2 Superlattice Films at the Low‐Annealing Temperature - Chuqian Zhu; Na Bai; Yufan Wang; Huajun Sun; Lanqing Zou; Yunhui Yi; Jiyang Xu; Jiawang Ren; Junming Zhang; Sheng Hu; Kanhao Xue; Lei Ye; et al. (Advanced Electronic Materials)
Abstract This study investigates the ferroelectric (FE) performance of [HfO2/ZrO2]6 superlattice FE capacitors using different top electrodes (TE). The unidirectional rapid thermal annealing (RTA) process from 450 to 600 °C is conducted. The device's remanent polarization (Pr) improved with TE hardness, and is maintained with harder TE at lower temperature. Furthermore, the superlattice's endurance and the recovery feature improve with harder TE. The increased orthorhombic phase (o‐phase) content and the decreased tetragonal phase (t‐phase) content indicate that the hard TE's out‐of‐plane stress at the interface suppressed the phase transition from the t‐phase to the monoclinic phase (m‐phase) and promotes the o‐phase formation. It's known that hard electrodes usually have low coefficient of thermal expansion (CTE), which can generate high in‐plane tensile strain optimizing the FE properties, so the lower‐CTE electrodes devices’ FE performances are expected to degrade more with temperature decreasing, which is opposite with the experimental results. Therefore, hard electrodes can generate high out‐of‐plane compressive stress to offset the reduced in‐plane tensile stress, leading to a FE compensation effect in low temperature thermal process.